Marrow-Infiltrating Lymphocytes – Role in Biology and Cancer Therapy - Borrello, Ivan; Noonan, Kimberly A. (Frontiers in Immunology, 2016)
The past several years have witnessed the acceptance of immunotherapy into the mainstream of therapeutics options for patients with various cancers. This has, in large part, been driven by the clinical successes of antibodies to the checkpoint inhibitors, CTLA-4 and PD-1, capable of imparting long-term clinical remissions in several solid tumors as well as Hodgkin’s lymphoma as well as the therapeutic successes of adoptive T cell transfer with chimeric antigen receptors (CARs) or modified T cell receptors that have mostly utilized peripheral T cells. One emerging area of therapeutic T cell interventions has been the utilization of marrow infiltrating lymphocytes (MILs) - a novel form of adoptive T cell therapy. This approach was initially developed to increase the likelihood of utilizing a precursor T cell population with an enhanced tumor specificity in bone marrow derived malignancies. However, the unique attributes of bone marrow resident T cells and their interaction with their microenvironment provides significant scientific rationale to potentially utilize these cells therapeutically in disease that extend beyond hematologic malignancies.